ANALISIS FAKTOR-FAKTOR YANG MENDORONG KEBERHASILAN USAHA PADA USAHA OPTIK DI ERA PANDAMI DI KOTA PADANG - Rina Novalinda; Dolly Iman Suryanta (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Abstract: Optical business is a business that supports health services that carry out the business of providing, storing and distributing optical devices. The optical business is an alternative business that has a fairly high prospect and is a business that continues to warm up. The purpose of this study was to determine the factors that influence the success of the Optics business in the city of Padang. The research method is correlational quantitative. The sample is 30 people. The data collection technique used a questionnaire with a Likert scale. Descriptive data analysis techniques, test requirements and hypothesis testing. The results of the study describe the data descriptively that the entrepreneurial knowledge of Padang City optical business actors is in the high category, entrepreneurial behavior is included in the good category and marketing strategies are in the good category. the success of the optical business of the city of Padang and the marketing strategy have an effect on the success of the optical business of the city of PadangKeywords: Entrepreneurial knowledge, marketing strategy behavior, business success.